Proximate, GC-FID, and micronutrient analysis of ex-tracts of azadirachta indica - Benjamin, Amadi; Mary, Emelieze; Charity, Ogunka-Nnoka; Nnabugwu, Agomuo; Peter, Amadi (International Journal of Advanced Chemistry, 2017)
Different extraction media applied on the pulverized leaves of Neem plant (Azadirachta indica) were analyzed for its proximate, phytochemical, and micronutrient compositions, predominantly using the gas chromatographic technique. The results showed that the ethanol extract contained the highest amounts of carbohydrates and fibre. No significant difference (p>0.05) was recorded for the protein and ash content of both ethanol and methanol extracts, while the moisture and fat contents occurred highest in aqueous and methanol extracts respectively. The phytochemical screening revealed the absence of glycosides in all the extracts while steroids were found only in methanol and ethanol extracts. The aqueous extracts contained greater amounts of epicate chin (13.42%), lunamarine (5.81%), tannin (19.18%) and phytates (0.27%), but lacked anthocyanin, phenol and kaempferol, while rutin (77.54%), ribalinidine (2.06%), oxalate (1.23%), anthocyanin (1.16%), and sparteine (0.05%) occurred highest in the ethanol extract. Only sparteine was lacking in the methanol extract. No significant difference was recorded between the aqueous and ethanol extracts for the vitamin A, D, C, and B2Â contents, while except for vitamin B3 (0.22mg/100g) and vitamin K (0.08mg/100g), 08mg/100g), the methanol extracts contained the least amounts of the vitamins evaluated. Manganese, zinc, copper, calcium and lead contents of the methanol extract were significantly higher than those of the other extracts while the aqueous extract contained the highest amount of sodium. This study has provided the scientific backing for the application of a specific extraction medium during the exploitation of distinct phytochemicals, while water, ethanol, and methanol should be the preferred extraction media for vitamins, proximate and dietary mineral contents respectively.Â